Hematopoietic stem cell transplantation therapy for refractory' Crohn disease: A systematic review and meta-analysis - Serrano-Fernandez, Victor; Carmona-Torres, Juan Manuel; Arroyo-Rodriguez, Almudena; Lopez-Gonzalez, Angel; Rabanales-Sotos, Joseba; Laredo-Aguilera, Jose Alberto (Medicine (Baltimore), 2024)
Background: Despite the availability of numerous treatments for Crohn disease, there are patients who do not respond to any therapy, thereby diminishing their quality of life. The aim of this review is to analyze the efficacy and safety of autologous hematopoietic stem cell transplantation therapy for refractory Crohn disease. Methods: This work is a systematic review with meta-analysis conducted in accordance with the guidelines of the Preferred Reporting Items for Systematic Review and Meta-Analyses. Electronic databases such as PubMed, Scopus, Web of Science, and ClinicalTrials were consulted. The searches were carried out in August 2024. To evaluate the efficacy of autologous hematopoietic stem cell transplantation in inducing remission, the mean and standard deviation of the Crohn's Disease Activity Index pre- and post- treatment were used, and a fixed-effects meta-analysis was conducted. Additionally, to assess the efficacy in perianal fistulas, a random-effects meta-analysis was performed, collecting data on the number of subjects with fistulas at the beginning and end of the intervention. All 95% confidence intervals were calculated, and the I2 statistic was used to assess the heterogeneity of the outcome variables. Results: A total of 609 records were identified from databases, with 12 studies selected for inclusion in the review. Immediate intervention proved effective in inducing a decrease in the Crohn Disease Activity Index compared to late intervention with conventional therapies. Moreover, the meta-analysis demonstrated efficacy for Crohn disease and associated fistulas with a mean decrease in the CDAI of −217.53 ± 14.3. When evaluating the efficacy of the procedure in perianal fistulas, a risk ratio of 0.47 with a 95% CI of [0.26, 0.86] was obtained. However, the procedure showed adverse effects, such as infections, acute renal failure or deaths. Conclusion: Systemic autologous hematopoietic stem cell transplantation has shown efficacy in patients who fail to achieve remission of their Crohn disease with conventional therapies. This procedure has also demonstrated efficacy in treating perianal fistulas. However, it is essential to carefully evaluate de implementation of this procedure due to the associated risks.